Honey as an immunomodulator during sepsis in animal model - Kassim, M.; Mansor, M.; Achoui, M.; Yan, O.S.; Devi, S.; Yusoff, K.M. (2009)
Malaysian honey (Gelam) has antibacterial activity and it also has a high antioxidant capacity and free radical scavenger activities. Honey extracts showed potent activity against TNFÎ± in L929 cell and NO in RAW 264.7 macrophage as well as inhibitory effects on the prostaglandin E2 and nitric oxide (NO) in inflammatory tissues of rat. Sepsis is mediated in part by bacterial endotoxin, which stimulates macrophages/monocytes to sequentially release early (for example, TNF, IL-1) cytokines and inducible enzymes such as inducible nitric oxide (iNOS) synthase and heme oxygenase 1 (HO-1) and late such as high-mobility group box 1 (HMGB1).